2012
DOI: 10.1673/031.012.11601
|View full text |Cite
|
Sign up to set email alerts
|

Proconiini Sharpshooters of Argentina, with Notes on Its Distribution, Host Plants, and Natural Enemies

Abstract: The American tribe Proconiini (Hemiptera: Cicadellidae: Cicadellinae) is one of the largest groups of xylem-feeding insects and includes the majority of the known vectors of xylem-born phytopathogenic organisms. The significance of the pathogens that this group transmits gives them an important role as pests, mostly for citrus fruit, grapes, and almonds. Knowledge of these Hemiptera in Argentina is insufficient and fragmentary. Thus one of the aims of this paper is to summarize the available information of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
18
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 22 publications
0
18
0
2
Order By: Relevance
“…Although adults of T. rubromarginata were collected from a wide range of host plants (31 species in 17 families) (Paradell et al, 2012), we only found egg masses of the sharpshooter on 12 species (belonging 10 families) out of 21 sampled. Similar results were reported for host plant preference of the glassy-winged sharpshooter, Homalodisca vitripennis Germar, whose adults and nymphs preferred to feed on plants that were not used as oviposition sites (Redak et al, 2004;Daane et al, 2004).…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Although adults of T. rubromarginata were collected from a wide range of host plants (31 species in 17 families) (Paradell et al, 2012), we only found egg masses of the sharpshooter on 12 species (belonging 10 families) out of 21 sampled. Similar results were reported for host plant preference of the glassy-winged sharpshooter, Homalodisca vitripennis Germar, whose adults and nymphs preferred to feed on plants that were not used as oviposition sites (Redak et al, 2004;Daane et al, 2004).…”
Section: Discussionmentioning
confidence: 91%
“…In addition, it has been shown that the mortality caused by egg parasitoids is the key factor in the population dynamics of many species of Auchenorrhyncha (Denno & Roderick, 1990). During the last decade, 25 species of egg parasitoids (Mymaridae, Trichogrammatidae, and Aphelinidae) were discovered affecting populations of T. rubromarginata in Argentina (Virla et al, 2008(Virla et al, , 2019Triapitsyn et al, 2008Triapitsyn et al, , 2010Paradell et al, 2012). It is known that host-parasitoid interactions take place in highly structured and complex environments, and that the structure of the host plant and diversity of the vegetation can affect the composition of the parasitoid complex, and their abundance (Obermaier et al, 2008;Kostenko et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tapajosa rubromarginata was an abundant species on citrus plants and weeds and positive for X. fastidiosa after the transmission assay, so could therefore be acting as vector of the bacterium in the orchards studied. Tapajosa rubromarginata is widely distributed in Argentina (Paradell et al., ) and considered a pest of the main agricultural crops, causing direct damage by feeding and oviposition (Remes Lenicov et al., ). Hortensia similis was predominant in weeds and positive for X. fastidiosa by both molecular methods; de Coll et al.…”
Section: Discussionmentioning
confidence: 99%
“…Cabeza cónica, obtusa; pronoto rugoso, con dos tuberosidades prominentes en los ángulos posteriores, margen posterior emarginado, escutelo rugoso; alas anteriores blancas, con un punto humeral y una línea oscura corta, aedeagus con un proceso basiventral bifurcado y curvado apicalmente. la parte proximal del ala; aedeagus con un par de procesos basales cortos y angulosos; paráfisis pares y largas en la base del aedeagus Paradell et al 2012)…”
unclassified